Cyclic cracking resistance of brittle materials in compressive loading - Lanin, A.G. (Проблемы прочности, 2009)
Fatigue behavior of brittle materials under compression is considered. The findings should be taken into account in the failure probability assessment of components made of materials with limited
plasticity, which are used in various stress states. Исследованы закономерности усталостного разрушения хрупких материалов в условиях циклического сжатия. Показано, что полученные результаты следует учитывать при оценке вероятности разрушения конструкционных элементов из материалов с ограниченным ресурсом пластичности при различных напряженных состояниях.